Peri- and postoperative morbidity and mortality in older patients with non-small cell lung cancer: a matched-pair study - Safi, Seyer; Gysan, Maximilian R.; Kronsteiner, Dorothea; Behnisch, Rouven; Muley, Thomas; Allgäuer, Michael; Winter, Hauke; Hoffmann, Hans; Eichhorn, Martin E. (World journal of surgical oncology, 2024)
Reports from case series suggest that operative outcomes are comparable amongst different age groups following surgery with curative intent for non-small cell lung cancer (NSCLC). The purpose of this study was to compare morbidity and mortality after NSCLC surgery in older patients (≥ 75 years) versus younger patients (< 75 years) and identify independent predictive risk factors. Methods: We identified 2015 patients with postoperative stages IA to IIIA according to AJCC/UICC 7th edition who had undergone NSCLC surgery with curative intent at a single specialized lung cancer center from January 2010 to December 2015. A matched-pair analysis was performed on 227 older patients and corresponding 227 younger patients. Short-term surgical outcomes were postoperative morbidity, length of hospital stay, 30-day and 90-day mortality. Long-term operative outcomes were disease-free and overall survival. Results: 454 patients were included in the matched-pair analysis. 36% of younger patients developed postoperative complications versus 42% in older patients (p = 0.163). Age was not significantly associated with the occurrence of postoperative complications. Median length of hospital stay was 14 days in older patients and 13 days in younger patients (p = 0.185). 90-day mortality was 2.2% in younger patients compared to 4% in older patients (p = 0.424). In patients aged 75 and older impaired performance status (ECOG ≥ 1) was associated with decreased overall survival (HR = 2.15, CI 1.34–3.46), as were preoperative serum C-reactive protein / albumin ratio ≥ 0.3 (HR = 1.95, CI 1.23–3.11) and elevated preoperative serum creatinine levels ≥ 1.1 mg/dl (HR = 1.84, CI 1.15–2.95). In the younger cohort male sex (HR = 2.26, CI 1.17–4.36), postoperative stage III disease (HR 4.61, CI 2.23–9.54) and preoperative anemia (hemoglobin < 12 g/dl) (HR 2.09, CI 1.10–3.96) were associated with decreased overall survival. Conclusions: Lung resection for NSCLC in older patients is associated with postoperative morbidity and mortality comparable to those of younger patients. In older patients, physical activity, comorbidities and nutritional status are related to survival and should influence the indication for surgery rather than age alone.